Exploring Speech Acts In "Heidi": An Analysis of Direct and Indirect Communication in Cinematic Dialogue - Emsa Anggy Puji Rahayu; Agwin Degaf; Nur Fitria Anggrisia (Journal of Pragmatics Research, 2024)
This research analyzes the use of speech acts in the movie Heidi, selected for its rich content and depiction of effective communication and moral values, particularly the importance of adaptation in a new environment. The character Heidi, a talkative young girl, provides valuable examples of how communication is established and maintained through her interactions. The study aims to identify the forms and meanings of speech acts used by the characters and to understand the interpretation of dialogues between speakers and hearers. The descriptive qualitative analysis method is employed to examine all utterances in Heidi that contain speech acts and speech strategies. The data are classified based on the forms of speech acts according to Wijana's theories and the meanings of speech acts using Searle's theory. The findings reveal the presence of various types of speech acts, including direct literal, direct nonliteral, indirect literal, and indirect nonliteral speech acts. Specifically, 133 utterances were analyzed and categorized into Representative (27), Directive (50), Expressive (31), Commissive (25), and Declarative (1). The study also shows that characters in the movie predominantly use directive speech acts. This research enhances the understanding of speech act theory and its application in film dialogues, emphasizing the importance of context and intention in interpreting communication.